Richard III : the self-made king - Hicks, Michael, 1948- (New Haven : Yale University Press, 2019)
The definitive biography and assessment of the wily and formidable prince who unexpectedly became monarch--the most infamous king in British history.
Preface -- List of illustrations -- List of abbreviations -- Pedigree 1: The royal line of succession -- 1. Myths ancient and modern: the shaping of Richard III -- 2. From infancy to adolescence: formative experiences 1452-68 -- 3. The young adult: the second war 1469-71 -- 4. Adult maturity: the king's servant 1471-5 -- 5. Forging the future 1471-83 -- 6. Lord of the north 1471-83 -- 7. Richard as `good lord' -- 8. Strategic foresight I: Gloucester's wish list 1477-8 -- 9. Career culmination: the Scottish war 1480-3 -- 10. Changing trajectories: the road to the crown 1483 -- 11. Richard III: the consolidation of the regime -- 12. The creation of an opposition: Buckingham's rebellion 1483 -- 13. Counterattack: rebuilding the regime 1483-5 -- 14. Strategic foresight II: so many enterprises -- 15. Setbacks and adversity 1483-5 -- 16. Defeat, disaster, and death: the battle of Bosworth -- Select bibliography -- Index.
Print version record; online resource viewed June 4, 2021.
JSTOR
Keywords: Richard -- III, -- King of England, -- 1452-1485.; Richard -- III, -- King of England, -- 1452-1485; Richard -- III. -- England, König -- 1452-1485; Great Britain -- Kings and rulers -- Biography; Great Britain -- History -- Richard III, 1483-1485.; Grande-Bretagne -- Histoire -- 1483-1485 (Richard III); Biography; Kings and rulers; Great Britain; Biography; 1483-1485; Biography; Biographies; History; Biographies; Biographies